Water quality in Malaysia: review Manik Urai, Durian and Geh rivers - Zaidi, Nur Syamimi; Tangahu, Bieby Voijant; Ersa, Ghina Rizqina; Wardhani, Widhowati Kesoema; Ramadhany, Putri; Hadibarata, Tony (Universitas Nahdlatul Ulama Surabaya, 2022)
Water pollution issues and clean water needs have forced developing countries, such as Malaysia. Relating to clean water demand for covering human activities, water quality index determine several water parameter that presents pollution problem in water. As a water source, clean water in river is a critical concern. River water quality is according to natural process and anthropogenic activities. River water is potential to be contaminated by industrial, domestic and agricultural activities. Thus, in this study, water quality and availability in Manik Urai, Durian and Geh rivers were reviewed. Each pollutants was investigated, for instance BOD, COD, DO, SS, and pH. Range of river water flow was also examined. Total water demand was mentioned. In addition, the impacts of drought in 1990-2016 were assessed. However, review resulted that climate change has severe impact in water supply system.